Oxidant and Antioxidant Status in Type 2 Diabetic Patients Before and After Therapy - Halifeoğlu, İhsan; Karataş, Fikret; Çolak, Ramis; Canatan, Halit; Telo, Selda (Fırat University, 2005)
Several studies reported that diabetic vascular complications and lipid peroxidation occur due to high blood glucose levels. Aim of the present study was to evaluate antioxidant status in type 2 diabetics (DM) before and after therapy. Levels of serum fasting glucose, malondialdehyde (MDA), lycopene, antioxidant vitamins (A, E, and C), triglycerid, total cholesterol, HDL- cholesterol, LDL- cholesterol, as well as eritrocyte HbA1C levels along with enzyme acitivity levels of superoxide dismutase (SOD), catalase (CAT) ve glutathion peroksidase (GSH-Px) were determined in thirty type 2 diabetic patients (19 man, 11 woman). After treatment period, reduction in blood glucose levels was accompanied with significant reduction in levels of HbA1C, MDA and triglycerid whereas there was significant increase in levels of CAT, SOD, vitamin A ve vitamin E. There was no statistically significant changes in levels of GSH-Px, vitamin C, lycopene, total cholesterol, HDL- cholesterol, LDL- cholesterol. Present results indicate that oxidative status developed due to hyperglycemia can be normalized by treatment. Treatment of diabetics who are educated by their attending doctors regarding their sickness will be much easier, this will affect the quality of diabetics positively, as a result financial burden on individuals and country will be minimized. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Kan glukoz düzeyinin yüksek seyretmesine bağlı olarak diabetik vaskülar komplikasyonlar ve lipid peroksidasyonunun meydana geldiği çok sayıda çalışmada rapor edilmektedir. Bu çalışmanın amacı; tip 2 diabetiklerde (DM) tedavi öncesi ve tedavi sonrası oksidatif durumu gözlemektir. 30 tip 2 diabetik hastadan (19 erkek ve 11 kadın) sağlanan örneklerde serum açlık kan glukoz, malondialdehit (MDA), likopen, antioksidan vitaminler (A, E ve C), trigliserit, total kolesterol, HDL-kolesterol, LDL-kolesterol düzeyleri, eritrositte HbA1C ile süperoksit dismutaz (SOD), katalaz (CAT) ve glutatyon peroksidaz (GSH-Px) enzim aktiviteleri tespit edildi. Tedavi sonrası dönemde kan glukoz düzeyindeki düşüşüne parelel olarak HbA1C, MDA ve trigliserit düzeylerinde anlamlı bir azalma gözlenirken; CAT, SOD, vitamin A ve vitamin E düzeylerinde anlamlı bir artış görüldü. GSH-Px, vitamin C, likopen , total kolesterol, LDL-kolesterol ve HDL-kolesterol düzeylerinde önemli bir değişiklik saptanmadı. Bu sonuçlar göstermektedir ki tip 2 diabetik kişilerde, hiperglisemiye bağlı olarak gelişen oksidatif durum, diyabetin tedavi edilmesi ile normale dönebilmektedir. Hastalıkları konusunda ilgili hekimler tarafından eğitilmiş diabetiklerin tedavileri daha kolay olacak, bu durumun da diabetiklerin yaşam kaliteleri olumlu etkileyerek hem kişiye hem de ülkeye getireceği mali külfeti azaltacaktır. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Tip 2 Diyabetik Hastalarda Tedavi Öncesi ve Tedavi Sonrası Oksidan ve Antioksidan Durum